2020
DOI: 10.1038/s41598-020-74051-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptomic analysis for linking acute stress responses to squamous cell carcinoma development

Abstract: Cutaneous squamous cell carcinoma (cuSCC) is the second most common skin cancer and commonly arises in chronically UV-exposed skin or chronic wounds. Since UV exposure and chronic wounds are the two most prominent environmental factors that lead to cuSCC initiation, we undertook this study to test whether more acute molecular responses to UV and wounding overlapped with molecular signatures of cuSCC. We reasoned that transcriptional signatures in common between acutely UV-exposed skin, wounded skin, and cuSCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Among them, MMP1, overexpressed in many cancers, was recently identified as a novel diagnostic and prognostic biomarker in head and neck SCC (NHSCC) [ 25 ]. In SCC, MMP1 is the most common upregulated marker found in previous studies [ 15 , 17 , 19 , 20 , 26 , 27 ]. Recently, Zheng et al, by comparing multiple datasets, confirmed that MMP1 may be pivotal to the transition from healthy tissue to premalignant lesions to SCC [ 28 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Among them, MMP1, overexpressed in many cancers, was recently identified as a novel diagnostic and prognostic biomarker in head and neck SCC (NHSCC) [ 25 ]. In SCC, MMP1 is the most common upregulated marker found in previous studies [ 15 , 17 , 19 , 20 , 26 , 27 ]. Recently, Zheng et al, by comparing multiple datasets, confirmed that MMP1 may be pivotal to the transition from healthy tissue to premalignant lesions to SCC [ 28 ].…”
Section: Discussionmentioning
confidence: 92%
“…Recent transcriptomic studies highlighted that even if a uniform histological criterion is used to diagnose AKs, there is a spectrum of AKs that, on the transcriptional level, resemble normal tissue versus some that resemble SCCs [ 15 , 16 , 17 , 18 ]. However, the low number of AK samples in these studies did not allow us to distinguish AK subclasses based on their transcriptional profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In OSM-knockout mice, cSCC tumor volume was reduced by approximately 30% when compared to wild-type mice after one month, however there were still significant amounts of IL-6, IL-1b, IL-23a, CXCL1, IL-4, and IFNg present in the tumor tissue compared to normal skin (194). The most understood environmental cause of cSCC is ultraviolet (UV) radiation (197). OSM signaling has been shown to suppress UV induce apoptosis of human keratinocytes and may be crucial towards early cancer progression in vitro via an increase in cell motility through ECM remodeling (197).…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…The most understood environmental cause of cSCC is ultraviolet (UV) radiation (197). OSM signaling has been shown to suppress UV induce apoptosis of human keratinocytes and may be crucial towards early cancer progression in vitro via an increase in cell motility through ECM remodeling (197). This indicates that OSM may not only be crucial for cSCC progression, but also may lead to a higher incidence of squamous cell carcinoma, via repression of apoptosis in keratinocytes.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%